A new seed-feeding species of Hemicolpus Heller, 1895 from south Brazil and redescription of Hemicolpus abdominalis Hustache, 1938 (Coleoptera: Curculionidae: Conoderinae) - Sanz-Veiga, Priscila A.; Savaris, Marcoandre; Leivas, Fernando W. T.; Da Silva Medeiros, Alexandre; Amorim, Felipe W. (Zootaxa, 2023)
The genus Hemicolpus Heller, 1895 (Curculionidae: Conoderinae) currently includes six species: H. cubicus (Lacordaire) (Brazil); H. heteromorphus Hustache (Brazil); H. abdominalis Hustache (Bolivia, Brazil, and Paraguay); H. costaricensis Hespenheide (Costa Rica); H. randiae Hespenheide (El Salvador and Mexico) and H. prenai Hespenheide (El Salvador and Mexico). The known species are predispersal seed predators whose larvae feed and develop within fruits of Rubiaceae. Species from Central America have been reared from the fruits of Randia L. (Rubiaceae). In contrast, the only host plant known for the South American species, H. abdominalis, is Tocoyena formosa (Cham. & Schltdl.) K. Schum. (Rubiaceae), a plant species widely distributed in the Cerrado biome, occurring from southeast to north and northeast of Brazil. Here, we describe a seventh species of Hemicolpus, H. maragatensis Sanz-Veiga, Savaris & Leivas, sp. nov., morphologically close to H. abdominalis, associated with fruits of Randia ferox (Cham. & Schltdl.) DC. in the south of Brazil. Furthermore, we designate a lectotype and provide a redescription of H. abdominalis, including additional characters to differentiate it from H. maragatensis. For both species, we provide morphological descriptions of external and internal characters, including male and female genitalia illustrations, distribution data, and notes on the biology and host plant. A barcode region of the mitochondrial DNA is also included for both species adding genetic information to the species characterization and differentiation. We also provide an identification key for the species of the genus.